2021
DOI: 10.47836/ifrj.28.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of citrus fibre and the prediction of oxidation in ground beef meatballs made with citrus fibre by ATR-FTIR spectroscopy with principal component analysis

Abstract: The objectives of the present work were (1) to determine the total polyphenol content (TPC), total flavonoid content (TFC), and oxygen radical absorbance capacity (ORAC) of citrus fibre, and (2) to predict, by attenuated total reflection (ATR)-Fourier transform infrared spectroscopy (FTIR), the oxidative stability of ground beef made with different levels (i.e., 0, 1, 3, and 5%) of citrus fibre (CF) during 1, 3, 5, or 7 days of refrigerated storage. The TPC, TFC, and ORAC values of citrus fibre were 3.753 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In the focused part of Figure 3 (a), the absorbance value of oils was decreased over time due to the production of peroxides between 2980-2880 cm -1 . Gedikoğlu et al (2021) examined the lipid oxidation in ground beef meatballs by FTIR spectra. They found that the absorbance decreased over time for the same band region.…”
Section: Resultsmentioning
confidence: 99%
“…In the focused part of Figure 3 (a), the absorbance value of oils was decreased over time due to the production of peroxides between 2980-2880 cm -1 . Gedikoğlu et al (2021) examined the lipid oxidation in ground beef meatballs by FTIR spectra. They found that the absorbance decreased over time for the same band region.…”
Section: Resultsmentioning
confidence: 99%